Thoughts for the Young Minds - Jalal, Asif. (New Delhi : Global Media Publications, 2009)
The book is an inspirational guide for Muslim teenagers navigating challenges of identity, faith, academic pressures, and societal prejudice. Drawing from his own experiences as a student and IPS officer, the author offers reflections on topics such as shaping destiny, balancing faith and education, resisting stereotypes, cultivating perseverance, leadership, and self-belief. Through a mix of personal narrative, philosophical insights, and actionable advice, the book aims to encourage young readers to anchor their life in meaning, overcome fear or self-doubt, and strive toward success with integrity.
Keywords: Muslim teenagers -- Conduct of life; Islamic Philosophy; Faith